2008
DOI: 10.1007/s00421-008-0918-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac response to exercise in young, normal weight and overweight men and women

Abstract: Overweight and obesity are associated with hemodynamic changes at rest. Whether these changes are mirrored during exercise is uncertain. We compared cardiac output (Q) and stroke volume (SV) in 12 overweight (OW) and 12 normal weight (NW) adults at rest and during exercise. Participants were assessed for body composition, peak oxygen consumption, and Q and SV at rest and during cycling exercise at 50, 75 and 100 W. Cardiac output was significantly higher at rest and during exercise in OW than NW when fat mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Vibration increased SV and cardiac indices to a greater extent in obese than lean women, which is in accordance with data reported in obese adults during voluntary aerobic exercise (Vella et al 2009). The greater increase in cardiac output index in our obese group could be the result of a reduced capacity for oxygen extraction, linked to alterations in glucose uptake and mitochondrial density reported in obesity (Kumagai et al 2002;Calbet & Lundby, 2012).…”
Section: Haemodynamic Responses During Vibration In Lean and Obese Womensupporting
confidence: 82%
See 2 more Smart Citations
“…Vibration increased SV and cardiac indices to a greater extent in obese than lean women, which is in accordance with data reported in obese adults during voluntary aerobic exercise (Vella et al 2009). The greater increase in cardiac output index in our obese group could be the result of a reduced capacity for oxygen extraction, linked to alterations in glucose uptake and mitochondrial density reported in obesity (Kumagai et al 2002;Calbet & Lundby, 2012).…”
Section: Haemodynamic Responses During Vibration In Lean and Obese Womensupporting
confidence: 82%
“…In the present study, we used WBV to examine the influence of mechanically induced contractions on the BP and HR responses and the baroreceptor sensitivity (BRS) in obese women. Based on findings in obese individuals using voluntary exercise modalities (Vella et al 2009;Dipla et al 2010), we hypothesized that obese women would exhibit increased central haemodynamic responses (stroke volume and cardiac output index) to passive WBV and an augmented BP response compared with their lean counterparts. In addition, we hypothesized that obese women would experience a blunted HR response, altered parasympathetic modulation and lower vasomotor ability during vibration compared with lean women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, characterizing and understanding the cardiac functional changes during exercise that occur with obesity are of emerging importance. We (Vella et al 2009) previously reported that young, overweight adults (mean BMI 29.3 kg m -2 , range 26-33 kg m -2 ) had higher cardiac output but similar VO 2 during submaximal exercise compared with age-and fitness-matched controls. These results suggest that oxygen extraction, rather than oxygen delivery (cardiac function) may be compromised in healthy, young, overweight subjects.…”
Section: Introductionmentioning
confidence: 90%
“…2) Significantly low resting PSD in obese compared to overweight with similar LF/HF and BRS in the 3 groups (Table 1) Increased muscle and adipose tissue mass of obese subjects may have high metabolic requirements leading to high SI and CI and low TPRI [32]. A study reported ethnicity and total fat mass adjusted high resting stroke volume (SV) and cardiac output (CO) in obese subjects compared to lean [34]. In comparison, we found significantly lower SI and CI and higher TPRI in overweight and obese with SI being the lowest in obese.…”
Section: Correlations Of Obesity Parameters With Hemodynamic Parametersmentioning
confidence: 99%